2016
DOI: 10.1016/j.cmet.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual Variation in DNA Methylation at a Putative POMC Metastable Epiallele Is Associated with Obesity

Abstract: Interindividual variation in DNA methylation at a putative POMC metastable epiallele is associated with obesity, Cell Metabolism (2016Metabolism ( ), doi: 10.1016Metabolism ( /j.cmet.2016 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(92 citation statements)
references
References 33 publications
6
79
0
7
Order By: Relevance
“…These regions were first described in mice, but subsequent human studies in Gambia have demonstrated epigenetic variation at metastable epialleles that are linked to periconceptional maternal nutrition 77 , findings that have later been replicated in a rural Bangladeshi cohort 78 . The methylation status of metastable epialleles has been linked to later obesity and metabolic function 79 .…”
Section: Periconceptional Mechanismsmentioning
confidence: 99%
“…These regions were first described in mice, but subsequent human studies in Gambia have demonstrated epigenetic variation at metastable epialleles that are linked to periconceptional maternal nutrition 77 , findings that have later been replicated in a rural Bangladeshi cohort 78 . The methylation status of metastable epialleles has been linked to later obesity and metabolic function 79 .…”
Section: Periconceptional Mechanismsmentioning
confidence: 99%
“…Missense mutations in the POMC and MC4R genes are associated with severe hyperphagic obesity syndromes that manifests within the first 1–2 years of life (Farooqi and O'Rahilly, 2008). The central nervous melanocortin system responds to environmental cues through epigenetic modifications that have long-lasting effects on expression of genes promoting lean phenotypes (Benite-Ribeiro et al, 2016; Kühnen et al, 2016). Methylation in a variably methylated region (VMR) of the POMC gene allele is associated with altered body mass in humans (Kühnen et al, 2016).…”
Section: An Overview Of the Central Nervous Melanocortin Systemmentioning
confidence: 99%
“…The central nervous melanocortin system responds to environmental cues through epigenetic modifications that have long-lasting effects on expression of genes promoting lean phenotypes (Benite-Ribeiro et al, 2016; Kühnen et al, 2016). Methylation in a variably methylated region (VMR) of the POMC gene allele is associated with altered body mass in humans (Kühnen et al, 2016). Methylation of this region is sensitive to metabolic conditions in utero , and to paternal methylation patterns.…”
Section: An Overview Of the Central Nervous Melanocortin Systemmentioning
confidence: 99%
“…Genetic effects cannot explain these rapid population shifts in obesity, though they can help to explain which individuals within any given population will be more or less susceptible. Recent research has revealed that epigenetic effects may explain a much greater proportion of population variance than genetic effects [10,11] and this has implications for prevention as discussed below. The Demographic Switch in Social Groups Most Susceptible to Obesity…”
Section: The Emergence Of Overweight and Obesity Worldwidementioning
confidence: 99%